Construct Validity of Non-Test Instrument for Problem-Based Learning Method - Septiana, Nova; Hermanto, Febrika Yogie (Journal of Office Administration : Education and Practice, 2024)
This study aims to examine how the process of problem-based learning emphasizes creativity, cooperative learning, critical thinking, and idea development. The instruments used in these assessments cannot reflect the principles inherent in the problem-based learning method, which prioritizes contextual and daily-life applications. The objectives of this study aim to validate the developed product using ADDIE model, focusing on the outcomes of assessments by instrument and learning evaluation experts. The results of this study showed that the assessment instrument was categorized as very feasible by experts with an average score of 4.59 of 5 as maximum score. The learning evaluation expert assessment score was 4.71, and the instrument expert assessment was 4.47. Thus, it can be stated that the products developed are valid and suitable for use by target group. Valid and feasible instruments are expected to provide more accurate student learning assessment results according to learning objectives.